DNA barcoding of selected species of pufferfishes (Order: Tetraodontiformes) of Puducherry coastal waters along south-east coast of India - Kaleshkumar, K.; Rajaram, R.; Vinothkumar, S.; Ramalingam, V.; Brajamani Meetei, Khangembam (Indian Journal of Fisheries, 2015)
Samples of three species of pufferfishes were collected from Puducherry in the south-east coast of India. Collected fishes were identified as Chilomycterus reticulatus, Arothron hispidus and Lagocephalus guentheri by mitochondrial CO1 gene sequencing. Neighbor-Joining method was used for phylogenetic analysis which confirmed that the analysed species had a dichotomous relationship with its ancestor species. Genetic variation was studied by sequence similarity using the homologous sequences retrieved from BLAST server. The maximum length of open reading frames (ORF) for the three pufferfish species viz., C. reticulatus, A. hispidus and L. guentheri were 171, 345 and 465 respectively. Results from a simple gene prediction algorithm revealed that C. reticulatus, A. hispidus and L. guentheri have 7 start codons each. The pairwise genetic distance calculated among the three species ranged from 0.002 to 0.176% for C. reticulatus, 0.002 to 0.169% for A. hispidus and 0.002 to 0.208% for L. guentheri. Genetic distance analysis of mitochondrial DNA sequences is demonstrated as unique to their related species of all pufferfishes. Genetic distance is also used in the comparison of genetic similarity between different species and also in different subspecies of pufferfishes belonging to the order Tetraodontiformes.